The fountains of Łódź: their relevance to the lives of its inhabitants - Bartnik, Adam; Suwart, Aleksandra (Turyzm/Tourism, 2015)
This paper presents the characteristics of the fountains of Łódź, their location in the public spaces of the city and changes in various time periods. Special attention is drawn to the function of fountains in contemporary cities and their social perception. Moreover, in the last part, the presumed reasons for their present distribution and typological variety are given.